Shoulder dystocia in babies born to Aboriginal mothers with diabetes: a population-based cohort study, 1998-2015 - Marwan Awad Ahmed; Helen D. Bailey; Gavin Pereira; Scott W. White; Kingsley Wong; Rhonda Marriott; Matthew J. L. Hare; Bridgette J. McNamara; Carrington C. J. Shepherd (BMC, 2024)
Abstract Background Australian Aboriginal and Torres Strait Islander women with diabetes in pregnancy (DIP) are more likely to have glycaemic levels above the target range, and their babies are thus at higher risk of excessive fetal growth. Shoulder dystocia, defined by failure of spontaneous birth of fetal shoulder after birth of the head requiring obstetric maneuvers, is an obstetric emergency that is strongly associated with DIP and fetal size. The aim of this study was to investigate the epidemiology of shoulder dystocia in Aboriginal babies born to mothers with DIP. Methods Stratifying by Aboriginal status, characteristics of births complicated by shoulder dystocia in women with and without DIP were compared and incidence and time-trends of shoulder dystocia were described. Compliance with guidelines aiming at preventing shoulder dystocia in women with DIP were compared. Post-logistic regression estimation was used to calculate the population attributable fractions (PAFs) for shoulder dystocia associated with DIP and to estimate probabilities of shoulder dystocia in babies born to mothers with DIP at birthweights > 3 kg. Results Rates of shoulder dystocia from vaginal births in Aboriginal babies born to mothers with DIP were double that of their non-Aboriginal counterparts (6.3% vs 3.2%, p < 0.001), with no improvement over time. Aboriginal mothers with diabetes whose pregnancies were complicated by shoulder dystocia were more likely to have a history of shoulder dystocia (13.1% vs 6.3%, p = 0.032). Rates of guideline-recommended elective caesarean section in pregnancies with diabetes and birthweight > 4.5 kg were lower in the Aboriginal women (28.6% vs 43.1%, p = 0.004). PAFs indicated that 13.4% (95% CI: 9.7%-16.9%) of shoulder dystocia cases in Aboriginal (2.7% (95% CI: 2.1%-3.4%) in non-Aboriginal) women were attributable to DIP. Probability of shoulder dystocia among babies born to Aboriginal mothers with DIP was higher at birthweights > 3 kg. Conclusions Aboriginal mothers with DIP had a higher risk of shoulder dystocia and a stronger association between birthweight and shoulder dystocia. Many cases were recurrent. These factors should be considered in clinical practice and when counselling women.